Design and fabrication of Ni/ZrO2 metal-ceramic functionally graded materials by a moving-magnetic-field-driving method - Jiasong Chang; Xiaoling Peng; Jing Li; Tristan Ellis (Journal of Materials Research and Technology, 2021)
Ni/ZrO2 metal-ceramic functionally graded materials (FGMs) have been successfully prepared using a moving-magnetic-field-driving method by moving a narrow distributed magnetic field from one end of the mixed slurry to the other end with the moving direction perpendicular to the field direction. The magnetic Ni particles follow the movement of the field and move in the slurry. After drying and sintering, Ni/ZrO2 FGMs with gradient composition distribution are successfully fabricated. The microstructures and the corresponding performance of Ni/ZrO2 FGMs are affected by many factors, such as solid content, magnetic field strength, moving velocity, cycle times, Ni content, particle size and also size ratio. The composition gradient of FGMs can be optimized by adjusting magnetic field parameters and constituent parameters. Compared with the preparation of FGMs by using a static gradient magnetic field, this field-driving method is more effective, attractive and easier to fabricate metal-ceramic FGMs, which is promising in scientific and technological applications.